(untitled) ("Journal "U". Economy. Management. Finance.", 2021)
The article analyzes the main indicators of the tourist and recreational industry of the Russian economy for the period 2011-2019, identifies the main trends and factors that determine the effectiveness of the decision-making system in the tourist and recreational complex: the level of effective demand; political and legal restrictions (sanctions regime, anti-pandemic travel restrictions, etc.), quality and range of manufactured tourism products; the tax regime substantiates recommendations for improving the efficiency of the management decision-making system. The reported study was funded by RFBR, project number 20-010-00820/